Non-viral gene therapy that targets motor neurons in vivo - Rogers, Mary-Louise; Smith, Kevin S.; Matusica, Dusan; Fenech, Matthew; Hoffman, Lee; Rush, Robert A.; Voelcker, Nicolas H. (Frontiers in Molecular Neuroscience, 2014)
A major challenge in neurological gene therapy is safe delivery of transgenes to sufficient cell numbers from the circulation or periphery. This is particularly difficult for diseases involving spinal cord motor neurons such as amyotrophic lateral sclerosis (ALS). We have examined the feasibility of non-viral gene delivery to spinal motor neurons from intraperitoneal injections of plasmids carried by ‘immunogene’ nanoparticles targeted for axonal retrograde transport using antibodies. PEGylated polyethylenimine (PEI-PEG12) as DNA carrier was conjugated to an antibody (MLR2) to the neurotrophin receptor p75 (p75NTR). We used a plasmid (pVIVO2) designed for in vivo gene delivery that produces minimal immune responses, has improved nuclear entry into post mitotic cells and also expresses green fluorescent protein (GFP). MLR2-PEI-PEG12 carried pVIVO2 and was specific for mouse motor neurons in mixed cultures containing astrocytes. While only 8% of motor neurons expressed GFP 72 h post transfection in vitro, when the immunogene was given intraperitonealy to neonatal C57BL/6J mice GFP specific motor neuron expression was observed in 25.4% of lumbar, 18.3% of thoracic and 17.0 % of cervical motor neurons, 72 h post transfection. PEI-PEG12 carrying pVIVO2 by itself did not transfect motor neurons in vivo, demonstrating the need for specificity via the p75NTR antibody MLR2. This is the first time that specific transfection of spinal motor neurons has been achieved from peripheral delivery of plasmid DNA as part of a non-viral gene delivery agent. These results stress the specificity and feasibility of immunogene delivery targeted for p75NTR expressing motor neurons, but suggests that further improvements are required to increase the transfection efficiency of motor neurons in vivo.